2019
DOI: 10.3390/ijms20071783
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Electrophiles as a Key Regulator for Endoplasmic Reticulum (ER) Stress

Abstract: The unfolded protein response (UPR) is activated by the accumulation of misfolded proteins in the endoplasmic reticulum (ER), which is called ER stress. ER stress sensors PERK, IRE1, and ATF6 play a central role in the initiation and regulation of the UPR; they inhibit novel protein synthesis and upregulate ER chaperones, such as protein disulfide isomerase, to remove unfolded proteins. However, when recovery from ER stress is difficult, the UPR pathway is activated to eliminate unhealthy cells. This signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…It has been reported that NO may regulate the ER stress through modifications of its chaperon proteins [41] however, lacunae exist. Among numerous chaperon the protein disulfide isomerase is most studied [46]. Besides this, NO could also nitrosylate the ER membrane located sensors of ER stress (PERK1, IRE1 and ATF6) [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that NO may regulate the ER stress through modifications of its chaperon proteins [41] however, lacunae exist. Among numerous chaperon the protein disulfide isomerase is most studied [46]. Besides this, NO could also nitrosylate the ER membrane located sensors of ER stress (PERK1, IRE1 and ATF6) [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In AD pathology, the correlation of NO and PDI has well suggested through complexities of unfolded protein responses [49]. In 2019, the emerging role of various electrophiles including NO has also been suggested as regulator of ER stress in various diseases [46]. Oxidative stress is correlated with impairment of mitochondrial functions and thus afflicted cellular physiology which could lead to the activation of chaperons and may subsequently initiate the ER stress and decide the cellular fate.…”
Section: Discussionmentioning
confidence: 99%
“…This can increase the exposure of hidden residues, rendering the protein more vulnerable to further modification [ 31 ]. As a result, the unfolded protein response (UPR) may be activated [ 67 , 68 , 69 , 70 ]. In addition, cross-linking or aggregation of proteins prevents their degradation via the 20S proteasome; inhibition of proteasome function may then occur, which directly affects cell viability and commonly results in cell death [ 71 , 72 ].…”
Section: Functional Consequences Of Lipoxidationmentioning
confidence: 99%
“…Recently, an emerging role of reactive electrophilic species (RES) as key regulators for the UPR, more specifically the IRE1 pathway, have been described [123]. Furthermore, RES have been reported to be involved in ER-stress related diseases, including neurodegenerative diseases, amyotrophic lateral sclerosis (ALS), and cancer [124,125,126].…”
Section: Therapeutic Approaches To Restore Protein Balancementioning
confidence: 99%